2018
DOI: 10.3390/molecules23040959
|View full text |Cite
|
Sign up to set email alerts
|

Using Peptidomimetics and Constrained Peptides as Valuable Tools for Inhibiting Protein–Protein Interactions

Abstract: Protein–protein interactions (PPIs) are tremendously important for the function of many biological processes. However, because of the structure of many protein–protein interfaces (flat, featureless and relatively large), they have largely been overlooked as potential drug targets. In this review, we highlight the current tools used to study the molecular recognition of PPIs through the use of different peptidomimetics, from small molecules and scaffolds to peptides. Then, we focus on constrained peptides, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 154 publications
(188 reference statements)
0
86
0
Order By: Relevance
“…26 There is therefore great interest in modifying these naturally occurring sequences in order to understand their binding properties and develop novel molecules with enhanced features. 3,27 A well-known example of linear peptides involved in transient protein-protein interactions comes from the Bcl-2 fam-ily of proteins. In human this family comprises five prosurvival members (Bcl-2, Mcl-1, Bfl-1, Bcl-x L , and Bcl-w) that interact with proapoptotic proteins comprising a ∼23-residue Bcl-2-homology-3 (BH3) motif.…”
Section: Linear Peptidesmentioning
confidence: 99%
“…26 There is therefore great interest in modifying these naturally occurring sequences in order to understand their binding properties and develop novel molecules with enhanced features. 3,27 A well-known example of linear peptides involved in transient protein-protein interactions comes from the Bcl-2 fam-ily of proteins. In human this family comprises five prosurvival members (Bcl-2, Mcl-1, Bfl-1, Bcl-x L , and Bcl-w) that interact with proapoptotic proteins comprising a ∼23-residue Bcl-2-homology-3 (BH3) motif.…”
Section: Linear Peptidesmentioning
confidence: 99%
“…4 Because of their size and complexity, macrocycles have demonstrated that they can bind with antibody-like affinity and specificity and successfully target PPIs. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Hence, macrocyclic molecules fill an important gap in the world of drugs between small molecules and larger biologics. 19,20 Significant progress has been made for peptides in terms of synthesis, formulation and delivery, 21 but their therapeutic value is partially limited due to their short in vivo half-life and lack of oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…There are a multitude of protein‐protein interactions in the cell that are mediated by ⍺‐helices, and in many disease states it would be advantageous to mimic features of an ⍺‐helix with a small molecule or peptide. A common strategy for mimicking ⍺‐helices has been through the use of constrained, helical peptides . Doing so provides for conformational stability by reducing the number of degrees of freedom of the peptide and/or by facilitating ⍺‐helical hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Others have published excellent recent reviews of the literature surrounding constrained helical peptides that focus on the application and future of constrained peptides on new macrocyclic constraints on biological activity, and on cysteine‐crosslinking, among others. The purpose of this review is to highlight recent structural advances in the development of new helix‐stabilizing technologies, constraint diversification, tether diversification, and combination strategies to create new bicyclic peptides (Figure ).…”
Section: Introductionmentioning
confidence: 99%